The Impact of Tariffs, Feeder, and Parking on Customer Engagement With Mediated Customer Satisfaction on Urban Railways - Agus Yulianto; Idris Gautama So; Edhie Budi Setiawan; Ocky Soelistio Pribadi (Dinasti Publisher, 2026)
To alleviate congestion in Jakarta, fast and clean public transport has been developed to encourage a modal shift toward environmentally friendly urban rail, namely the Mass Rapid Transit (MRT) and Light Rail Transit (LRT). Currently, the Jakarta LRT, the Jabodebek LRT, and the Jakarta MRT are in operation. The key challenge is persuading users of private cars, motorcycles, and conventional public transport to adopt the LRT and MRT for daily trips, thereby reducing congestion. This study examines the effects of fares, feeder buses, and parking facilities on customer engagement, with customer satisfaction as a mediating variable in Jakarta’s urban rail system. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach (SEM-PLS). The sample comprised 220 LRT and MRT users. The results show that fares and feeder services have positive and significant effects on customer satisfaction but positive yet insignificant effects on customer engagement. Parking exerts a positive and significant influence on both customer satisfaction and engagement. Customer satisfaction also has a positive and significant effect on customer engagement. Furthermore, fares, feeder services, and parking have positive and significant indirect effects on customer engagement through customer satisfaction.